Study of phase distribution in pipe cyclonic compact separator using wire mesh sensor - Kanshio, Sunday; Yeung, Hoi; Lao, Liyun (Elsevier, 2016)
Separation of gas–liquid mixture, which is achieved by using either large gravity separators or compact separators is a common and vital operation in the petroleum industry. Where space and cost are key project considerations, gas–liquid compact separators are very attractive because of their versatility and cost effectiveness. Efficient performance of the cyclonic separator depends on smooth and steady swirling flow. Unsteady swirling flow in the separator may be due to capacity constraint, improper design or unforeseen flow instability at the inlet. An understanding of phase distribution in gas discharge section of these separators would help design engineers make a better decision when selecting and sizing inlet nozzle, diameter and length of the separator. In this paper, the structure of phase distribution and liquid holdup in the gas discharge section of the separator was obtained using a 24x24 resolution wire mesh sensor (WMS). The acquired area average liquid holdup and the images were analysed using time series and 2D slice to discriminate between partial separation and critical separation condition. The liquid holdup as a function of separator inlet superficial velocity was quantified.
Keywords: Subsea separation; Swirling flow; Cyclonic separator; Liquid holdup; Phase distribution; Wire mesh sensor